Teknologi Imersif dalam Pendidikan Jasmani: Penerapan Assemblr EDU terhadap Kegembiraan Peserta Didik SD - Gazali, Zeinol; Kartiko, Dwi Cahyo; Ridwan, Mochamad (MAN Insan Cendekia Jambi, 2025)
This study aims to determine how much influence the application of Assemblr EDU media has on students' excitement about physical fitness material in Physical Education, Sports and Health (PJOK) subjects for 5th grade students of SDN Sidotopo I/48 Surabaya. The method used is quantitative with a One Group Pretest-Postest design. The study population was 5th grade students of SDN Sidotopo I/48 Surabaya. The research sample consisted of 30 students from class 5C. Data was collected through pretest and posttest questionnaires. Data analysis included Normality test and Paired Sample T-Test conducted using SPSS Version 25. The results showed a significant effect of using Assemblr edu media on students' excitement in physical fitness material. Obtained an average pretest of 56.23 and posttest of 65.57, an increase of 17%. The data in this study have been tested for normality and the data are normally distributed. The Paired Sample T-Test test obtained is the Sig value. (2-tailed) excitement is 0.000. This means that the sig value <0.05 So it is concluded that there is an effect of using Assemblr edu media on the excitement of students in learning PJOK on physical fitness material in elementary schools.